2009
DOI: 10.1007/s11060-009-9877-5
|View full text |Cite
|
Sign up to set email alerts
|

‘Putting our heads together’: insights into genomic conservation between human and canine intracranial tumors

Abstract: Numerous attributes render the domestic dog a highly pertinent model for cancer-associated gene discovery. We performed microarray-based comparative genomic hybridization analysis of 60 spontaneous canine intracranial tumors to examine the degree to which dog and human patients exhibit aberrations of ancestrally related chromosome regions, consistent with a shared pathogenesis. Canine gliomas and meningiomas both demonstrated chromosome copy number aberrations (CNAs) that share evolutionarily conserved synteny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 57 publications
(84 reference statements)
4
81
0
Order By: Relevance
“…Meningiomas in both species are highly comparable and share similar phenotypes and gene expression profiles [116,121,123]. Genomic profiling of canine meningiomas for DNA copy number by Thomas et al [11] indicated that canine meningiomas share a limited extent of whole chromosome aneuploidy with their human counterpart. Importantly, the authors hypothesized that by considering the DNA copy number data from both species, the shared aberrations should be the focus of research; for example, in this study they were able to reduce the size of conserved genomic segments by as much as 50-fold.…”
Section: (I) Meningiomamentioning
confidence: 99%
“…Meningiomas in both species are highly comparable and share similar phenotypes and gene expression profiles [116,121,123]. Genomic profiling of canine meningiomas for DNA copy number by Thomas et al [11] indicated that canine meningiomas share a limited extent of whole chromosome aneuploidy with their human counterpart. Importantly, the authors hypothesized that by considering the DNA copy number data from both species, the shared aberrations should be the focus of research; for example, in this study they were able to reduce the size of conserved genomic segments by as much as 50-fold.…”
Section: (I) Meningiomamentioning
confidence: 99%
“…As might be expected based on data in humans, there is decreased genomic instability in canine meningiomas compared to generally more aggressive gliomas. Potential similarities to human tumors have been documented including loss of canine chromosome (CFA) 17 and 27 (CFA 17, 27), syntenic to human chromosome (HSA) 1p and 12p; HSA 1, 12 in meningiomas 133, 134…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…27 This marker deserves investigation in diagnosis of gliomas in dogs and cats, although these species seem to have their own unique mutational tumor profiles. 129 …”
Section: Oligodendrogliomamentioning
confidence: 99%